Cost and health impact analysis of herpes zoster vaccination in Norway. (17th February 2022) - Flem, Elmira; Graham, Jonathan; Yi, Zinan; Wisløff, Torbjørn; Johnson, Kelly D.
ABSTRACT: Background: A decision analytic model was developed to estimate the cost-effectiveness of a national vaccination program against herpes zoster in Norway. Methods: The model analyzed six vaccination scenarios that included the live-attenuated zoster vaccine under different target ages of vaccination (60, 65, and 70 years) compared with no vaccination. A catch-up program implemented in the first year of the vaccination was included in three of the scenarios. The model followed the population of Norway over a 40-year time horizon to estimate costs and outcomes associated with vaccination. Immunization costs, costs related to herpes zoster (both healthcare sector and non-healthcasre sector), the quality of life gains due to avoided cases of herpes zoster, and quality-of-life losses due to vaccine-related adverse events were estimated. Results and Conclusions: A national vaccination program would result in reduction of the number of herpes zoster cases and decreased burden of illness. Vaccinating adults at 65 years of age with catch-up up to 70 years in the first year of the program was the most cost-effective strategy with the incremental cost per quality-adjusted life-year gained at NOK (Norwegian Krone) 245, 459 from the societal perspective and NOK 248, 637 from the health care system perspective.